Isolation and Identification of Cellulose Degrading Bacteria from Banana Peel Compost - P., Yendania Grevitara; F., Badriyatur Rahma; P., Hellen Septirangga; Y., Irma Dahlia; Suarsini, Endang (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2018)
Cellulolytic bacteria are bacteria that have the ability to hydrolyze cellulose complexes into smaller oligosaccharides and eventually become glucose. Glucose is used as a carbon and energy source for bacterial growth. This study was conducted to isolate the cellulose degrading bacteria from banana peel compost that produce cellulose enzymes based on the clear zone that visible around the colony. The cellulolytic activity was determined by the ability of bacteria to hydrolyze the Carboxymethyl Cellulose (CMC) substrate. Determination of cellulolytic activity is known based on cellulolytic index calculation, the diameter total minus the diameter of the colony and divided by the diameter of the colony. The result of five bacterial isolates was found but only one bacterium had the potential to be a cellulose degradation. Based on the Microbact Gram-Negative Identification System, the bacterium is Burkholderia cepacia. These bacteria have an important role in nature as decomposers of various complex compounds, such as cellulose, hemicellulose, lignin, and pectin.